PEMANFAATAN ARTIFICIAL INTELLIGENCE DALAM PROGRAM PELATIHAN DAN PENGEMBANGAN KARYAWAN - Firdaus; Dodi Setiawan Riatmaja; Iriana Bakti; Nur Azizah; Windy Permata Suyono; Andi Zulfikar Darussalam (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
In the era of digital transformation, the use of Artificial Intelligence (AI) in employee training and development programs is increasingly becoming a key focus for companies in improving the effectiveness and efficiency of human resources. AI has the ability to analyze performance data, personalize training materials, and provide real-time feedback, thus accelerating the process of improving employee skills. This research aims to analyze the role of AI in optimizing training programs, identifying the benefits and challenges faced in its implementation. The method used in this research is a literature study and secondary data analysis from various previous studies. The results show that the use of AI in employee training can increase engagement, accelerate the learning curve, and enable a data-driven approach to training decision-making. However, challenges such as employee resistance, limited technological infrastructure, and the need for ethical and privacy regulations are still barriers to the widespread application of AI. Therefore, companies need to develop the right strategies in integrating AI into the training system to improve competitiveness and workforce productivity.